2021
DOI: 10.1016/j.tourman.2020.104233
|View full text |Cite
|
Sign up to set email alerts
|

Event portfolio management: An emerging transdisciplinary field of theory and praxis

Abstract: The phenomenon of event portfolio has gradually received acceptance and recognition as host destinations are steadily moving towards assembling multiple events across the calendar to serve multiple policy purposes. This paper reviews all the pertinent literature providing a common ground for studying event portfolios and their management exigencies. It traces the origins of the event portfolio concept and outlines its evolution to date. It thus, maps out event portfolio management as a complex emergent field, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 108 publications
(173 reference statements)
0
16
0
Order By: Relevance
“…Ziakas (2020) proposes a theoretical model integrating the holistic event portfolio approach with the leverage perspective. More recently, Ziakas and Getz (2021) conduct a literature review determining the origins of the event portfolio concept and its evolution to date.…”
Section: Sports Event Portfolios: a Global Strategy For The Economic ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ziakas (2020) proposes a theoretical model integrating the holistic event portfolio approach with the leverage perspective. More recently, Ziakas and Getz (2021) conduct a literature review determining the origins of the event portfolio concept and its evolution to date.…”
Section: Sports Event Portfolios: a Global Strategy For The Economic ...mentioning
confidence: 99%
“…More recently, Ziakas and Getz (2021) carry out an in-depth review of the literature in the field of event portfolios, identifying a slow-evolving process that needs integration and further collection of empirical evidence. The current article confirms this situation and contributes with a classification of the portfolios of events analyzed in the literature (see Table 1).…”
Section: Sports Event Portfolios: a Global Strategy For The Economic ...mentioning
confidence: 99%
“…These areas of high relatedness can then be cross-leveraged in order to capture synergistic benefits that would not have otherwise been accessible to the destination (Pereira et al, 2015). There remains, however, a lack of empirical research into the determinants of visitors' expenditure across an event portfolio (Ziakas and Getz, 2021). Furthermore, the range and quality of data needed to apply the resulting models is frequently unavailable in practice (Getz and McConnell, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Three years after that, how to devise a strategic portfolio of events based on cross-leveraging remained, according to Mariani and Giorgio (2017, p.90) an "impenetrably black box". Only this year, Ziakas and Getz (2021) published an 'exhaustive' review of the event portfolio literature and still found no empirical studies that attempted to take the theory and put it into practice. The present study therefore aims to contribute to the literature by examining a real-life case study of an event portfolio, particularly with regard to how ex-post analysis can be used to good effect and to emphasise the essential strategic role of the DMO.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies having been published to date that recommend the adoption of a strategic portfolio approach to marketing and managing events at the destination level (Getz & Page, 2016;Ziakas, 2010Ziakas, , 2013aZiakas & Costas, 2010, 2011aZiakas & Getz, 2021), and the undeniably strong theoretical basis for wishing to do so (Ziakas, 2010(Ziakas, , 2013aZiakas & Costas, 2010Ziakas & Getz, 2021), there remains an absence of studies to demonstrate how such strategic portfolios can best be formulated and developed (Pereira, Mascarenhas, Flores & Pires, 2015). Indeed, the feasibility and relative utility of different techniques for implementing an effective event portfolio remains a subject that has been almost entirely unexplored in the extant literature (Antchak, 2017;Clark & Misener, 2015;Dickson, Milne & Werner, 2018;Whitford, 2004Whitford, , 2009Whitford, Phi & Dredge, 2014;Ziakas, 2014).…”
Section: Introductionmentioning
confidence: 99%